PENGARUH LITERASI FINANSIAL DAN EFIKASI DIRI YANG DIMEDIASI OLEH PROGRAM CINTA BANGGA PAHAM RUPIAH TERHADAP PERILAKU KEUANGAN SISWA DI SMP NEGERI 5 SEMARANG SEBAGAI SEKOLAH MITRA BANK INDONESIA - Wulansari, Rossita; Dwi Cahyaningdyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the influence of financial literacy and self-efficacy on students’ financial behavior, with the Cinta Bangga Paham (CBP) Rupiah Program as a mediating variable among students at SMP Negeri 5 Semarang. Utilizing a quantitative explanatory approach with Partial Least Square (PLS) analysis, data were collected from 353 students via questionnaires. The analysis results demonstrate that: (1) financial literacy and self-efficacy have a significant positive effect on financial behavior; (2) the CBP Rupiah Program acts as a mediator, strengthening the effect of both on financial behavior; (3) all research instruments fulfill validity and reliability criteria; and (4) the research model yields R-square values of 63.3% for financial behavior and 69.4% for the CBP Rupiah variable. These findings emphasize the importance of integrating nationally based financial education programs to shape students’ financial behavior from an early age.